Ψυχοκοινωνική αποκατάσταση ατόμων με παγιωμένη ψυχική νόσο : Επιστροφή στην κοινότητα - Γιώργος, Αλεξάνδρου (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Τhe effectiveness of the Community Mental Health Services providing care to people with established mental illness has not been assessed sufficiently, Purpose: The purpose of this study was to investigate the effectiveness of the community mental health services in the psychosocial rehabilitation of persons with consolidated mental illness after about deinstitutionalization. Material and method: The method used in this study was the search of relevant Greek and English literature in databases such as the EMBASE and PUBMED. The keywords used in this search were psychosocial rehabilitation, deinstitutionalisation, long-stay patients, community mental health services, social functioning, psychiatric reform and clinical and social outcomes. Finally 7 research studies were included. Results: The community mental health services have played a key role in the improvement of people with consolidated mental illness after their deinstitutionalisation. Regardless that though, the research data regarding the degree of the effectiveness of such services are contradictory. In most cases a reduction of relapse and of the re-entering was noticed. Conclusions: Community structures of mental health services play a crucial role in the psychosocial rehabilitation of people with consolidated mental illness. However, a more detail study regarding the effectiveness of these methods is needed, using quantitative and qualitative design.
Keywords: Community Mental Health Services; Mental disorders; Health care reform; Rehabilitation--Psychological aspects; Phyciatric nursing